PERAN SEKTOR PERTANIAN DALAM PEREKONOMIAN KABUPATEN MOROWALI - Abd Aziz,M,R Yantu, Arifudin Lamusa, Iksan (AGROTEKBIS, 2015)
This study was to determine (1) the tendency of change in the economy of agricultural sector at Morowali regency , (2) the role of agriculture sector in the economy of Morowali, and (3) the role of agricultural sector of Morowali in Central Sulawesi. Secondary data was collected from governmental offices or offices related to this study, at Regency and Provincial levels. Results of the analysis showed that the agricultural sector is identified as the basis for the analysis of the sector, with the highest LQ value of 3.106 (2009) and the lowest value of 2.064 LQ (2003) and plantation sector with the highest LQ value of 1,817 (2009) and the lowest value of 1.474 LQ (2013). Contribution of the agricultural sector and subsector to Morowali, the highest was 44.62 billions (2009) and the lowest is 29.99 billion (2013), the Morowali Regency's agricultural sector contributed at the highest was 10.77 (2013) and the lowest was 10.05 billions (2009) to the Central Sulawesi's agricultural sector